Manajemen Komunikasi Pariwisata Di Desa Bukit Kabupaten Bengkulu Tengah - Arifin, Zainal; Octaviani, Vethy; Sari, Sapta (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
This study aims to determine tourism communication management in Bukit Village, Semidang Lagan District, Central Bengkulu Regency. Data collection techniques were carried out using interviews with research informants. There were four informants in this study, namely the Village Head, Chairman of the Village Representative Body, Chairman of Youth Organization and Secretary of BumDes as the manager of Curug Cay waterfall tourist attraction. Data analysis techniques using qualitative descriptive analysis consisting of data reduction, presentation and conclusions. The results of research on tourism communication management in Bukit Village, Semidang Lagan Subdistrict, Central Bengkulu Regency are seen based on management theory according to George R. Terry (Rosady Ruslan 2006: 158-159) which consists of Planning, Organizing, Actuating and Controlling. It can be seen that the communication management carried out by Bukit Village in the development of special tourism attraction Curug Cay waterfall is already through the development planning mechanism which begins with a plan to build a concrete rebate road, build a restroom, make stairs to the tourist attraction including the construction of parking lots. Organizing all stakeholders is done by conducting annual meetings even twice a year to ensure that each institution, both the village government, BPD, BumDes and the community and youth can carry out their main duties and functions. In the movement carried out by the BumDes, the construction of facilities and infrastructure has been carried out in accordance with the planning. This is done so that every visitor can feel comfortable in traveling. The supervision or evaluation is carried out by the village government and the chairman of the BPD and the community in an annual meeting after hearing reports from the BumDes. Monthly reports by BumDes are also carried out as a form of responsibility for the funds it manages..